The state of external respiration in higher education students suffering from bronchial asthma - Babenko , K. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. The most common respiratory diseases throughout the world include chronic obstructive and allergic diseases, in particular, asthma. Bronchial asthma is one of the most urgent social issues. Studies have shown that otherwise practically healthy students demonstrate a reduced external respiratory function, in particular, vital capacity of the lungs and forced vital capacity of the lungs, as well as Tiffeneau index, against the background of the reduced motor activity. Students with bronchial asthma also tend to reduce their motor activity as a result of distance learning and unresolved issues regarding the peculiarities of adapted physical education. The implementation of health improvement and health preservation technologies into physical education becomes particularly important for students with bronchial asthma, primarily for improving the functional state of the respiratory organs. Purpose of the study. Investigation of the respiratory function of higher education students with bronchial asthma. Research methods. There were examined 25 healthy and 61 first-year students with asthma aged (17.8±0.78). Girls predominated among the examinees: 60,7 %. The duration of asthma ranged from 2 to 7 (4.4±0.2) years. The spirometry method was used to measure the main parameters characterising lung volumes and capacities: it determined respiratory volume, maximum lung ventilation, vital capacity of the lungs, proper vital capacity of the lungs, as well as the volume of forced exhalation in the first second and the FEV1/VC ratio – the Tiffeneau index (%). Results. The study has shown that the external respiratory function was insuficient in 91.8% of students. Satisfactory function of the respiratory system was observed in 13.5% of young women. All young men had the disorder of external breathing. More than a third of students demonstrated a 1.6-time (р<0,001) decrease in respiratory volume, 1.3-time (р<0,001) reduction of vital lung capacity. At the level of the middle bronchi (MEF50), almost a quarter of students demonstrated a 1.4-time (р<0,001) reduction of air flow volumetric speed, which happened under insuficient chest excursion (r=0,84; p=0,001) and was associated with insuficient physical activity (r=0,85; p=0,001). In separate cases, this parameter reduced significantly and demonstrated a 1.9-time decrease (р<0,0001). At the level of small bronchi, MEF75 was decreased in 59.0% of patients. A moderate reduction of 1.4 times (р<0,001) occurred more often than a significant reduction of 1.8 times (р<0,0001). Therefore, the violation of the patency of the respiratory tract was most often observed at the level of large and small bronchi.